Kajian Penentuan Pembayaran Dam Menurut Beberapa Mazhab yang dilakukan Jamaah Haji Indonesia - Muhammad Farrel Ghiffary; Mukhsin Ahmad (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
Hajj is one of the pillars of Islam that must be carried out by all Muslims for those who can afford it. The implementation of the hajj of course has pillars and conditions that regulate the implementation of the hajj, if they commit an offense that is not in accordance with the pillars of hajj, then a Muslim or Muslim woman can be sanctioned. In the implementation of the Hajj, the sanctions given are called dam. The research was conducted to find out the views of the top four Islamic imams on the payment of fines (dam) in the implementation of the Hajj, the types of violations that can be imposed and to see the development of the implementation of Hajj for Indonesian pilgrims. The research was carried out using qualitative methods. The subject of the study is an Indonesian hajj pilgrim guide who has done it. The four major sects (Hanafi, Maliki, Shafi'i, Hambali) agree that dam is a fine of worship that must be paid when pilgrims violate the prohibition or abandon the obligation of Hajj, with the main form of slaughtering animals, feeding the poor, or fasting if they are unable to afford it. The difference lies in the limit of a violation so that it is obligatory and a choice between slaughter, food alms, and fasting in each sect.